2015
DOI: 10.1016/j.bios.2014.07.050
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-controlled microintaglio printing for high-resolution micropatterning of RNA molecules

Abstract: We have developed an advanced microintaglio printing method for fabricating fine and high-density micropatterns and applied it to the microarraying of RNA molecules. The microintaglio printing of RNA reported here is based on the hybridization of RNA with immobilized complementary DNA probes. The hybridization was controlled by switching the RNA conformation via the temperature, and an RNA microarray with a diameter of 1.5 µm and a density of 40,000 spots/mm(2) with high contrast was successfully fabricated. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…[103] A microintaglio printing method for RNA arraying has been optimized, by exploiting the complementarity of the DNA probes with the RNA sequences. [104] Finally, more complex structures of RNA, in particular RNA aptamers, can be deposited on solid supports by inkjet printing, without any loss of functionality. [105] However, the lower chemical stability of RNA oligonucleotides with respect to DNA, and the possibility to use equivalent complementary DNA (cDNA) sequences has limited the use of RNA in printing.…”
Section: Nucleic Acidsmentioning
confidence: 99%
“…[103] A microintaglio printing method for RNA arraying has been optimized, by exploiting the complementarity of the DNA probes with the RNA sequences. [104] Finally, more complex structures of RNA, in particular RNA aptamers, can be deposited on solid supports by inkjet printing, without any loss of functionality. [105] However, the lower chemical stability of RNA oligonucleotides with respect to DNA, and the possibility to use equivalent complementary DNA (cDNA) sequences has limited the use of RNA in printing.…”
Section: Nucleic Acidsmentioning
confidence: 99%
“…This approach was further improved using poly(dimethylsiloxane) (PDMS) for the creation of a soft lithography-based microintaglio printing method to generate high-density protein arrays ( 78 ). A year later, temperature controlled microintaglio printing (TC-μTP) was developed and used to generate RNA microarrays using DNA-immobilized magnetic beads ( 79 ). The second and very similar method that aimed to improve the density of protein arrays uses on-chip micro compartmentalization of protein synthesis in arrayed micrometer scale chambers from confined DNA template molecules ( 80 ).…”
Section: Screening Of Proteins On 2d Microarraysmentioning
confidence: 99%
“…To accomplish high-contrast µIP, we have recently introduced an advanced form of µIP by controlling the adsorption and/or printing reaction of the presynthesized ink molecules via a thermal trigger (Figure 5) [30]. This is based on a controllable hybridization reaction between a presynthesized messenger RNA and a substrate-immobilized complementary DNA probe by switching the ability of the messenger RNA to fold into a secondary structure via the temperature during µIP processing.…”
Section: Microintaglio Printing-based Biomolecular Microarraysmentioning
confidence: 99%
“…Therefore, temperature switching before and after the press-sealing step in the µIP process can prevent the undesired printing of presynthesized messenger RNA molecules in the non-array region (Figure 5a). Using this method, we reported the fabrication of transcribed RNA microarrays with a diameter of 1.5 µm and a density of 40,000 spots per mm 2 with high contrast (Figure 5b,c) [30]. Most importantly, we also demonstrated that the uniformity of patterned signals over a range of microarray feature sizes spanning one order of magnitude is not affected, and thus, this method can be used for the miniaturization of arrays to obtain high-density nanoarrays.…”
Section: Microintaglio Printing-based Biomolecular Microarraysmentioning
confidence: 99%